High-strength soluble aluminum-based composite material and preparation method thereof
By adding specific elements to aluminum-based composite materials and using semi-continuous casting and high-energy electromagnetic treatment technology, high-strength soluble aluminum-based composite materials were prepared, which solved the problems of reduced mechanical properties and uncontrollable dissolution rate in high temperature and high pressure environments, and achieved the effect of high mechanical properties and controllable dissolution rate.
Patent Information
- Application Number
- CN202410480481.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-04-22
- Publication Date
- 2025-04-29
- Estimated Expiration
- 2044-04-22
AI Technical Summary
The mechanical properties of existing soluble aluminum alloys are reduced in high temperature and high pressure environments, making them difficult to use in fracturing environments with high requirements such as deep well mining, and the dissolution rate is uncontrollable, which cannot meet the mechanical indicators and time requirements required for operation.
By adding elements such as Zn, Mg, Cu, Ga, In, Sn, Zr, Sc and SiCp to the aluminum-based composite material, combined with semi-continuous casting process and high-energy electromagnetic treatment technology, a high-strength soluble aluminum-based composite material was prepared. The composition and preparation process design of this material can significantly improve the mechanical properties of the material and the controllability of the dissolution speed.
A soluble aluminum alloy material with high mechanical properties and controllable dissolution speed in high temperature and high pressure environments has achieved a room temperature tensile strength of 560-580MPa, an elongation after break of 3-5%, and a dissolution rate of 100-150mg/cm2/h in a neutral aqueous solution environment of 93℃ and 3% KCl, and its performance index is ahead of existing soluble aluminum alloys.
Smart Images

Figure CN118326214B_ABST
Abstract
Description
Technical Field
[0001] The invention specifically discloses a high-strength soluble aluminum-based composite material and a preparation method thereof, and relates to the technical field of nonferrous metal preparation. Background Art
[0002] The exploitation of low-permeability unconventional oil and gas resources such as shale gas and shale oil mainly relies on technologies such as hydraulic fracturing. The fracturing process requires the use of downhole tools such as fracturing balls and bridge plugs to seal the construction pipes of different operating layers. These downhole tools are made of soluble alloys, which can dissolve in the downhole environment after the operation is completed, eliminating manual drilling and recycling processes, reducing engineering risks and construction costs, and significantly improving construction efficiency and the recovery rate of oil and gas fields. Therefore, the research and development of soluble alloys has attracted much attention in the industry. However, extreme environments such as high temperature and high pressure have put forward higher requirements for the comprehensive performance of soluble alloys.
[0003] Aluminum-based composite materials have comprehensive properties such as high specific strength, high specific rigidity, high wear resistance and excellent high temperature resistance, and are widely used in aerospace, national defense and military industries. Soluble aluminum alloys mainly improve the solubility of alloys by adding low-melting point activation elements such as Ga, In, and Sn to aluminum alloys. However, adding too many low-melting point elements to form a second phase compound with a low melting point will deteriorate the mechanical properties of the alloy. Therefore, the mechanical properties of soluble aluminum alloys with good solubility are not high, and the high temperature resistance is poor. Under high temperature and high pressure conditions, the tensile strength, hardness and other mechanical properties of the material are reduced, and it is easy to deform severely, making it difficult to use in fracturing environments with high working conditions such as deep well mining. In addition, the dissolution rate of soluble aluminum alloys is accelerated under high temperature conditions, and the controllability is poor. It cannot provide the mechanical index requirements required for work and the effective time required to complete the operation, which greatly limits its scope of use.
[0004] CN114717456A discloses a high-temperature soluble aluminum alloy and a preparation method thereof, wherein the composition of each element is, by weight percentage: Mg 1.5wt%, Ga 0.1wt%, In 0.7wt%, Sn 0.6wt%, and the balance is Al and unavoidable impurity elements, and the tensile strength of the high-temperature soluble aluminum alloy is 120-140MPa and the elongation is 25-30%; the preparation method thereof is prepared by smelting and casting, hot extrusion treatment, solution heat treatment, and aging treatment, but the room temperature tensile strength of the prepared soluble aluminum alloy is only 120-140MPa, which is difficult to meet the use requirements. Based on the idea that the composition of the composite material reinforcement can be flexibly set, the development of high-performance soluble aluminum-based composite materials is expected to solve the technical difficulties faced by unconventional energy efficiency mining. At present, there are no reports on the research and patents on high-strength soluble aluminum-based composite materials and their preparation methods. Summary of the invention
[0005] In order to solve the above technical problems, the present invention provides a high-strength soluble aluminum-based composite material and a preparation method thereof, which provides a soluble aluminum alloy material with high mechanical properties and controllable dissolution rate in a fracturing environment with high working requirements such as deep well mining.
[0006] In order to achieve the above object, the present invention provides a high-strength soluble aluminum-based composite material, the components of which are calculated by weight percentage:
[0007] Mg0.8%-2.0%, Zn6.0%-10.0%, Cu0.5%-1.0%, Ga0.5%-3.0%, In0.3%-0.8%, Sn0.3%-0.8%, Zr0.1%-0.2%, Sc0.1%-0.2%, SiCp0.01%-8.0%, and the balance is Al.
[0008] More preferably, the high-strength soluble aluminum-based composite material comprises, by weight percentage:
[0009] Mg1.0%-2%, Zn6%-8.0%, Cu0.5%-0.9%, Ga0.5%-1.0%, In0.4%-0.6%, Sn0.35%-0.6%, Zr0.11%-0.15%, Sc0.15%-0.2%, SiCp6%-8.0%, and the balance is Al. More preferably, the high-strength soluble aluminum-based composite material comprises the following components by weight percentage:
[0010] Mg1.5%, Zn7.0%, Cu0.7%, Ga0.6%, In0.4%, Sn0.35%, Zr0.11%, Sc0.2%, SiCp8.0%, and the balance is Al.
[0011] More preferably, the SiCp particle size is 0.5-2.0 µm.
[0012] The present invention also provides a method for preparing the high-strength soluble aluminum-based composite material, comprising the following steps:
[0013] (1) Melting treatment: Melting under atmosphere protection, pure aluminum, Al-Cu master alloy, Al-Zr master alloy, Al-Sc master alloy are melted, pure Zn, pure Mg, pure Sn, pure In, pure Ga are added in sequence for melting, and after all the alloys are melted, degassing and filtering are performed, and the refined melt is kept warm;
[0014] (2) Alloy casting: First, the aluminum alloy melt prepared in step (1) is continuously injected into the crystallizer of a semi-continuous casting machine to cast rods, and then a high-volume SiC / aluminum alloy is continuously added to the alloy melt in the form of a wire billet. Finally, a high-energy electromagnetic treatment device is turned on to perform electromagnetic treatment on the alloy melt during the casting process to obtain cast rods of the required specifications.
[0015] (3) Extrusion forming: the high-strength soluble aluminum-based composite material cast rod prepared in step (2) is homogenized and then hot-extruded to obtain an extruded material of desired specifications;
[0016] (4) Heat treatment: The high-strength soluble aluminum-based composite extrusion material prepared in step (3) is heat treated, cut to size according to the weight of the parts, and machined into the required downhole tools such as fracturing balls and bridge plugs.
[0017] Furthermore, in step (1), the temperature of the melt to which pure Zn, pure Mg, pure Sn, pure In and pure Ga are added is 730-750°C; the temperature for degassing and filtering treatment is 725-735°C; and the holding time of the melt after refining is 15-20 minutes.
[0018] Furthermore, the atmosphere protection in step (1) is an inert gas protection, such as argon, nitrogen, etc.
[0019] Furthermore, in step (2), the casting speed of the rod casting process is 100-200 mm / s, the cooling rate is 3.0-8.0°C / s, the magnetic induction intensity of the electromagnetic treatment process is 300-500 Gauss, and the shear rate is 1400-3000 rpm.
[0020] Furthermore, in step (3), the extrusion temperature is 420-460° C., the extrusion speed is 0.5-1.0 mm / s, and the extrusion ratio is 9-12.
[0021] Furthermore, in the heat treatment of step (4), the solution treatment temperature is 400-430°C, the solution treatment time is 0.5-1.0h, the aging treatment temperature is 110-130°C, and the aging time is 12-16h.
[0022] The beneficial effects of the present invention are:
[0023] (1) The addition of Zn, Mg and Cu elements in the present invention can significantly improve the mechanical properties of the soluble aluminum-based composite material. Zn and Mg can form MgZn2 strengthening phase to play a precipitation strengthening role; Cu can increase the dispersion of the precipitation phase in the matrix. At the same time, the inventors also found that Cu, as a cathode metal, forms a microscopic galvanic cell with Al to accelerate the dissolution of the alloy.
[0024] (2) The addition of Zr and Sc elements in the present invention can significantly improve the structure and performance of the soluble aluminum-based composite material. The Al3X phase generated during the solidification process can significantly refine the grains as heterogeneous nucleation particles, improve the uniform distribution of the second phase, and achieve fine grain strengthening while also facilitating the uniform dissolution of the alloy. The secondary Al3X phase precipitated during the homogenization process can significantly increase the recrystallization temperature of the alloy, playing a role in inhibiting recrystallization and dispersion strengthening; the addition of low-melting-point elements Ga, In, and Sn in the present invention can significantly improve the solubility of the soluble aluminum-based composite material. Ga, In, and Sn form a second-phase compound with a low melting point, which destroys the dense oxide film structure formed on the Al surface, exposing the highly active Al, causing it to continuously react with water and dissolve.
[0025] (3) The addition of SiC particles in the present invention can significantly improve the strength and stiffness of the soluble aluminum alloy, especially the high-temperature mechanical properties. However, the inventors found in experiments that the SiC particles evenly distributed at the grain boundaries will automatically fall off during the dissolution process, which can not only increase the dissolution rate of the soluble aluminum alloy, but also reduce the addition amount of low-melting-point elements Ga, In, and Sn. The addition of low-melting-point elements will lead to deterioration of mechanical properties. Therefore, the addition of SiC particles takes into account both the solubility and mechanical properties of the material.
[0026] (4) The present invention introduces a high-energy magnetic field to perform shear stirring treatment on the melt in the preparation of high-strength soluble aluminum-based composite materials, which can not only force the SiC particles to be evenly dispersed, but also significantly refine and homogenize the matrix structure of the aluminum-based composite material, thereby simultaneously improving the mechanical properties and uniform solubility performance of the aluminum-based composite material.
[0027] (5) The high-strength soluble aluminum-based composite material prepared by the present invention has comprehensive properties such as high mechanical properties and controllable dissolution rate. The room temperature tensile strength is 560-580 MPa, the elongation after break is 3-5%; the dissolution rate under the environmental conditions of 93°C and 3% KCl neutral aqueous solution is 100-150 mg / cm 2 / h, and its performance indicators are leading in soluble aluminum alloys. The present invention adopts a semi-continuous casting process to produce cast rods in the preparation of high-strength soluble aluminum-based composite materials. The method has the advantages of low production cost, high material utilization rate, and easy large-scale production. It can be applied to downhole tools such as fracturing balls and bridge plugs in fracturing environments with high working conditions such as deep well mining and oil and gas field efficiency enhancement. BRIEF DESCRIPTION OF THE DRAWINGS
[0028] Figure 1 This is a schematic diagram of preparing high-strength soluble aluminum-based composite material casting rods according to the present invention.
[0029] Among them, 1. Semi-continuous casting machine; 2. Aluminum alloy melt; 3. SiC / aluminum alloy wire billet; 4. Electromagnetic processing equipment. DETAILED DESCRIPTION
[0030] The technical scheme in the embodiments of the present invention will be clearly and completely described below in conjunction with the accompanying drawings of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, rather than all the embodiments. The equipment used in the preparation method of the present invention can adopt the well-known equipment in the art. The raw materials used in the present invention are commercially available unless otherwise specified. Example 1
[0031] High-strength soluble aluminum-based composite material, the components are composed by weight percentage:
[0032] Mg1.5%, Zn7.0%, Cu0.7%, Ga0.6%, In0.4%, Sn0.35%, Zr0.11%, Sc0.2%, SiCp8.0%, and the balance is Al.
[0033] The preparation method of the above-mentioned high-strength soluble aluminum-based composite material is as follows:
[0034] (1) Alloy smelting: Smelting is carried out under the protection of argon atmosphere. First, pure aluminum, Al-Cu master alloy, Al-Zr master alloy, and Al-Sc master alloy are melted. Then, when the melt temperature reaches 730°C, pure Zn, pure Mg, pure Sn, pure In, and pure Ga are added in sequence for smelting. After all the alloys are melted, they are kept at 730°C for 1 hour for degassing and filtration.
[0035] (2) Casting: First, the aluminum alloy melt 2 processed in step (1) is continuously poured into a semi-continuous casting machine 1 for casting. Figure 1 As shown, the casting speed is 120 mm / s and the cooling rate is 5.0 °C / s. After the casting process is stable, the wire feeding device is turned on to continuously add high volume fraction SiC / aluminum alloy into the alloy melt in the form of wire billet 3, and the SiCp particle size is 1.0-2.0 µm. At the same time, the high-energy electromagnetic treatment equipment 4 is turned on to shear and stir the alloy melt during the casting process. The magnetic induction intensity is 400 mT and the shear rate is 1800 rpm, so as to prepare a Φ203 mm high-strength soluble aluminum-based composite material cast rod.
[0036] (3) Extrusion forming: The prepared high-strength soluble aluminum-based composite material cast rod is subjected to homogenization treatment and then hot extrusion forming. The billet extrusion temperature is 450°C, the extrusion speed is 0.5 mm / s, and the extrusion ratio is 9, thereby obtaining a Φ70 mm high-strength soluble aluminum-based composite material extrusion material.
[0037] (4) Heat treatment: The prepared high-strength soluble aluminum-based composite extrusion material is subjected to solution aging heat treatment at a solution temperature of 420°C for a solution time of 1.0 h, an aging temperature of 130°C for an aging time of 12 h. The heat-treated material is cut to size according to the weight of the part and machined into the required fracturing balls and bridge plugs. Example 2
[0038] High-strength soluble aluminum-based composite material, the components are composed by weight percentage:
[0039] Mg0.8%, Zn6.0%, Cu0.5%, Ga0.5%, In0.3%, Sn0.3%, Zr0.1%, Sc0.1%, SiCp0.01%, and the balance is Al.
[0040] The preparation method of the above-mentioned high-strength soluble aluminum-based composite material is as follows:
[0041] (1) Alloy smelting: Smelting is carried out under the protection of argon atmosphere. First, pure aluminum, Al-Cu master alloy, Al-Zr master alloy, and Al-Sc master alloy are melted. Then, when the melt temperature reaches 730°C, pure Zn, pure Mg, pure Sn, pure In, and pure Ga are added in sequence for smelting. After all the alloys are melted, they are kept at 730°C for 1 hour for degassing and filtration.
[0042] (2) Casting: First, the aluminum alloy melt treated in step (1) is continuously poured into a semi-continuous casting machine for casting, with a casting speed of 100 mm / s and a cooling rate of 3.0 °C / s. After the casting process is stable, the wire feeding device is turned on to continuously add high-volume SiC / aluminum alloy into the alloy melt in the form of wire billets, with a SiCp particle size of 0.5-1.5 µm. At the same time, the high-energy electromagnetic treatment equipment is turned on to shear and stir the alloy melt during the casting process, with a magnetic induction intensity of 300 mT and a shear rate of 1400 rpm, to prepare a Φ203 mm high-strength soluble aluminum-based composite material cast rod.
[0043] (3) Extrusion forming: The prepared high-strength soluble aluminum-based composite material cast rod is subjected to homogenization treatment and then hot extrusion forming. The billet extrusion temperature is 420°C, the extrusion speed is 1.0 mm / s, and the extrusion ratio is 12 to obtain a Φ70 mm high-strength soluble aluminum-based composite material extrusion material.
[0044] (4) Heat treatment: The prepared high-strength soluble aluminum-based composite extrusion material is subjected to solution aging heat treatment at a solution temperature of 400°C for a solution time of 0.5 h, an aging temperature of 110°C for an aging time of 16 h. The heat-treated material is cut to size according to the weight of the part and machined into the required fracturing balls and bridge plugs. Example 3
[0045] High-strength soluble aluminum-based composite material, the components are composed by weight percentage:
[0046] Mg2.0%, Zn10.0%, Cu1.0%, Ga3.0%, In0.8%, Sn0.8%, Zr0.2%, Sc0.2%, SiCp6%, and the balance is Al.
[0047] The preparation method of the above-mentioned high-strength soluble aluminum-based composite material is as follows:
[0048] (1) Alloy smelting: Smelting is carried out under the protection of argon atmosphere. First, pure aluminum, Al-Cu master alloy, Al-Zr master alloy, and Al-Sc master alloy are melted. Then, when the melt temperature reaches 750°C, pure Zn, pure Mg, pure Sn, pure In, and pure Ga are added in sequence for smelting. After all the alloys are melted, they are kept at 730°C for 1 hour for degassing and filtration.
[0049] (2) Casting: First, the aluminum alloy melt treated in step (1) is continuously poured into a semi-continuous casting machine for casting, with a casting speed of 120 mm / s and a cooling rate of 5.0 °C / s. After the casting process is stable, the wire feeding device is turned on to continuously add high-volume SiC / aluminum alloy into the alloy melt in the form of wire billets, with a SiCp particle size of 1.0-2.0 µm. At the same time, the high-energy electromagnetic treatment equipment is turned on to shear and stir the alloy melt during the casting process, with a magnetic induction intensity of 400 mT and a shear rate of 1800 rpm, to prepare a Φ203 mm high-strength soluble aluminum-based composite material cast rod.
[0050] (3) Extrusion forming: The prepared high-strength soluble aluminum-based composite material cast rod is subjected to homogenization treatment and then hot extrusion forming. The billet extrusion temperature is 450°C, the extrusion speed is 0.5 mm / s, and the extrusion ratio is 9, thereby obtaining a Φ70 mm high-strength soluble aluminum-based composite material extrusion material.
[0051] (4) Heat treatment: The prepared high-strength soluble aluminum-based composite extrusion material is subjected to solution aging heat treatment at a solution temperature of 420°C for a solution time of 1.0 h, an aging temperature of 130°C for an aging time of 12 h. The heat-treated material is cut to size according to the weight of the part and machined into the required fracturing balls and bridge plugs. Example 4
[0052] High-strength soluble aluminum-based composite material, the components are composed by weight percentage:
[0053] Mg1.0%, Zn8.0%, Cu0.9%, Ga1.0%, In1.0%, Sn0.6%, Zr0.15%, Sc0.15%, SiCp7%, and the balance is Al.
[0054] The preparation method is the same as that in Example 1.
[0055] Comparative Example 1
[0056] High-strength soluble aluminum-based composite material, the components are composed by weight percentage:
[0057] Mg4.0%, Zn10.0%, Cu1.0%, Ga3.0%, In0.8%, Sn0.8%, Zr0.2%, Sc0.2%, SiCp6%, and the balance is Al.
[0058] The preparation method is the same as that in Example 3.
[0059] Comparative Example 2
[0060] High-strength soluble aluminum-based composite material, the components are composed by weight percentage:
[0061] Mg2.0%, Zn10.0%, Cu2%, Ga3.0%, In0.8%, Sn0.8%, Zr0.2%, Sc0.2%, SiCp6%, and the balance is Al.
[0062] The preparation method is the same as that in Example 3.
[0063] Comparative Example 3
[0064] High-strength soluble aluminum-based composite material, the components are composed by weight percentage:
[0065] Mg0.8%, Zn6.0%, Cu0.5%, Ga0.5%, In0.3%, Sn0.3%, Zr0.1%, Sc0.1%, and the balance is Al.
[0066] The preparation method is the same as that in Example 2.
[0067] Comparative Example 4
[0068] High-strength soluble aluminum-based composite material, the components are composed by weight percentage:
[0069] Mg1.5%, Zn7.0%, Cu0.7%, Ga0.6%, In3%, Sn0.35%, Zr0.11%, Sc0.2%, SiCp8%, and the balance is Al.
[0070] The preparation method is the same as that in Example 1.
[0071] Comparative Example 5
[0072] High-strength soluble aluminum-based composite material, the components are composed by weight percentage:
[0073] Mg0.8%, Zn6.0%, Cu0.3%, Ga0.5%, In0.3%, Sn0.3%, Zr0.1%, Sc0.1%, SiCp0.01%, and the balance is Al.
[0074] The preparation method is the same as that in Example 2.
[0075] The performance test results of the embodiments and comparative examples are shown in the following table:
[0076]
[0077] The dissolution rate is under the environmental conditions of 93° C. and 3% KCl neutral aqueous solution.
[0078] The above is only a preferred embodiment of the present invention, and does not limit the present invention in other forms. Any technician familiar with the profession may use the above disclosed technical content to change or modify it into an equivalent embodiment with equivalent changes. However, any simple modification, equivalent change and modification made to the above embodiment according to the technical essence of the present invention without departing from the technical solution of the present invention still belongs to the protection scope of the technical solution of the present invention.
Claims
1. A high-strength soluble aluminum-based composite material, characterized in that: The composition by weight percentage includes: Mg1.0%-2%, Zn6%-8.0%, Cu0.5%-0.9%, Ga0.5%-1.0%, In0.4%-0.6%, Sn0.35%-0.6%, Zr0.11%-0.15%, Sc0.15%-0.2%, SiCp6%-8.0%, the balance is Al; The room temperature tensile strength is 420-580MPa, and the elongation after break is 3-5%; the dissolution rate under the environmental conditions of 93℃ and 3% KCl neutral aqueous solution is 100-150mg / cm 2 / h, used for the preparation of oil and gas resource extraction tools.
2. A high-strength soluble aluminum-based composite material according to claim 1, characterized in that: The composition by weight percentage includes: Mg1.5%, Zn7.0%, Cu0.7%, Ga0.6%, In0.4%, Sn0.35%, Zr0.11%, Sc0.2%, SiCp8.0%, and the balance is Al.
3. The high-strength soluble aluminum-based composite material according to any one of claims 1 to 2, characterized in that: The SiCp particle size is 0.5-2.0 μm.
4. A method for preparing a high-strength soluble aluminum-based composite material, characterized in that: The high-strength soluble aluminum-based composite material according to any one of claims 1 to 3 comprises the following steps: (1) Melting treatment: Melting under inert atmosphere protection, pure aluminum, Al-Cu master alloy, Al-Zr master alloy, Al-Sc master alloy are melted, pure Zn, pure Mg, pure Sn, pure In, pure Ga are added in sequence for melting, and after all the alloys are melted, degassing and filtering are performed, and the refined melt is kept warm; (2) Alloy casting: First, the aluminum alloy melt prepared in step (1) is continuously injected into the crystallizer of a semi-continuous casting machine to cast rods, and then a high-volume SiC / aluminum alloy is continuously added to the alloy melt in the form of a wire billet. Finally, a high-energy electromagnetic treatment device is turned on to perform electromagnetic treatment on the alloy melt during the casting process to obtain cast rods of the required specifications. (3) Extrusion forming: the high-strength soluble aluminum-based composite material cast rod prepared in step (2) is homogenized and then hot-extruded to obtain an extruded material of desired specifications; (4) Heat treatment: The high-strength soluble aluminum-based composite extrusion material prepared in step (3) is heat treated, cut to size according to the weight of the part, and machined into the required tool.
5. The method for preparing the high-strength soluble aluminum-based composite material according to claim 4, characterized in that: The temperature of the melt to which pure Zn, pure Mg, pure Sn, pure In and pure Ga are added in step (1) is 730-750°C; the temperature for degassing and filtering treatment is 725-735°C; and the holding time of the melt after refining is 15-20 minutes.
6. The method for preparing a high-strength soluble aluminum-based composite material according to claim 4, characterized in that: In the alloy casting process of step (2), the casting speed is 100-200 mm / s, the cooling rate is 3.0-8.0°C / s, the magnetic induction intensity of the electromagnetic treatment process is 300-500 Gauss, and the shear rate is 1400-3000 rpm.
7. The method for preparing a high-strength soluble aluminum-based composite material according to claim 4, characterized in that: In the extrusion forming of step (3), the extrusion temperature is 420-460° C., the extrusion speed is 0.5-1.0 mm / s, and the extrusion ratio is 9-12.
8. The method for preparing a high-strength soluble aluminum-based composite material according to claim 4, characterized in that: In the heat treatment of step (4), the solution treatment temperature is 400-430°C, the solution treatment time is 0.5-1.0h, the aging treatment temperature is 110-130°C, and the aging time is 12-16h.
Citation Information
Patent Citations
High-strength degradable aluminum alloy and preparing method and application thereof
CN108251721A
Preparation method of particle-reinforced indium-free soluble aluminum-based composite material
CN114959409A